Effectiveness of competitive activity of high class hockey players accounting a level of their self-esteem - Mikhnov, A. P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: study the effect of increasing the level of self-esteem on the efficiency of competitive activity of high class players.